Aid for Trade flows and Wage Inequality in the manufacturing sector of recipient-countries - Sèna Kimm Gnangnon (ZBW – Leibniz Information Centre for Economics, 2020)
The present article aims to contribute to the literature on the effectiveness of Aid for Trade (AfT) flows in recipient-countries by investigating the effect of these resource flows on wage inequality in the manufacturing sector of recipient-countries. The analysis has shown that AfT interventions help reduce wage inequality in the manufacturing sector of countries that liberalize their trade policies, enjoy greater trade openness, experience higher exports of labour-intensive, low-skill and high skill manufacturing products. Additionally, AfT interventions contribute to dampening the negative effect of export product concentration (for example on primary products) on wage inequality in the manufacturing sector. Finally, AfT flows reduce wage inequality in the manufacturing sector of countries that import manufacturing products (including machinery and transport equipment goods) or enjoy a greater extent of multilateral trade liberalization.
Keywords: F35; F13; F14; J3; 330; Aid for Trade; Wage inequality in the manufacturing sector